Answer:
The correct answer is A) 2
Step-by-step explanation:
In order to find this, input 1 into the equation for each value of x that you see.
f(x) = x^2 + 3x - 2
f(1) = 1^2 + 3(1) - 2
f(1) = 1 + 3 - 2
f(1) = 2
Answer:
3
5
÷
j
=
3
8
Multiply the numerator of the first fraction by the denominator of the second fraction. Set this equal to the product of the denominator of the first fraction and the numerator of the second fraction.
(
3
5
)
⋅
8
=
j
⋅
3
Step-by-step explanation:Multiply the numerator of the first fraction by the denominator of the second fraction. Set this equal to the product of the denominator of the first fraction and the numerator of the second fraction.
(
3
5
)
⋅
8
=
j
⋅
3
Your answer would be C. 2
As a mixed number it’s 7 6/9 -not too sure about improper fraction. just know that repeating decimals always have a 9 as the denominator -hope that helps :)